Retention and tolerance of autoreactive CD4+ recent thymic emigrants in the liver. (January 2015) - Xu, Xi; Zhang, Shusong; Jin, Rong; Wang, Ke; Li, Pingping; Lin, Liang; Dong, Jie; Hao, Jie; Zhang, Yan; Sun, Xiuyuan; Pang, Xuewen; Qian, Xiaoping; et al.
Abstract: Mechanisms of peripheral tolerance play a critical role in preventing T cells that escape from negative selection in the thymus from initiating autoimmune reactions. To investigate the site of peripheral tolerance induction, we examined migration and activation of recent thymic emigrants (RTEs) in liver, spleen, lymph node and peripheral blood. We show that a fraction of RTE precursors were retained in the liver independent of the secondary lymphoid organs. Compared to RTEs from the lymph nodes, RTEs from the liver proliferated more and many exhibited an activated phenotype with the capability of producing IL-10 upon activation. Liver RTEs also responded poorly to interleukin (IL)-7 and were more prone to apoptosis. Following transfer into RAG −/− recipients, liver RTEs induced more severe inflammation and T cell infiltration in the lung and colon. The extrathymic expression of MHC and Aire is required for the acquisition of tolerogenic phenotype of newly generated thymic emigrants in the liver. These results suggest that the liver is the first checkpoint in the periphery to filter, retain, and enforce tolerance to autoreactive CD4 + thymic emigrants that escape from negative selection. Highlights: Some CD4 + recent thymic emigrants (RTEs) were retained in the liver independent of secondary lymphoid organs. Liver CD4 + RTEs induced more severe inflammation than lymph node RTEs when transferred into RAG1 −/− mice. Liver RTEs responded poorly to IL-7, were more prone to apoptosis, and produced higher level of IL-10 upon activation. The extrathymic expressions of MHC and Aire contributed to the acquisition of tolerogenic phenotype of liver RTEs.